Enhancing Speaking Skills through Dialogue Card Media in Drama-Based Language Learning - Salsabina, Salsabina; Suwadi, Suwadi; Rosidah, Ilmiyatur (Actual Insight, 2025)
This study investigates the effectiveness of dialogue card media in enhancing students’ speaking skills through drama-based language learning among eleventh-grade students at PGRI 2 Pasuruan Vocational High School. Preliminary observations revealed limited opportunities for role-play and dialogue presentation, resulting in low levels of speaking competence. The lack of engaging media further hindered student interaction and motivation. To address this issue, the study was grounded in a constructivist pedagogical approach that emphasizes active participation and scaffolding as essential to language skill development. A descriptive qualitative design was employed, with data collected through classroom observations, student questionnaires, and documentation. Data analysis involved reduction, display, and conclusion drawing. The results demonstrated that the use of dialogue card media significantly improved students’ speaking performance. Learners showed active engagement during all stages of learning listening, discussing, and enacting dialogues and the majority achieved speaking scores between 80 and 90. These findings suggest that dialogue card media can serve as an effective and interactive instructional tool, particularly in vocational education settings, by promoting communication skills through dynamic, drama-based learning experiences. The study offers practical implications for language teachers seeking innovative strategies to foster communicative competence. Future research may expand on these findings by applying dialogue card media in diverse educational contexts and subject areas.